Youth sports coaches' knowledge, knowledge construction, and coaching behaviors - Na, J. (Research Quarterly for Exercise and Sport, 2009)
The purpose of this study was to analyze youth sports coaches' understanding of their coaching; specifically how youth sports coaches perceive their coaching knowledge in terms of coaching philosophy, goals and strategies, how youth sports coaches construct their own knowledge, and how coaching knowledge is reflected in their coaching behaviors.